1990
DOI: 10.1055/s-2007-1024800
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mineral Content of Junior Competitive Weightlifters

Abstract: It is suggested that practicing various sports can increase the bone mineral content (BMC). However, we were unable to find any reports indicating BMC changes in weightlifting, a sport which involves both extremities and spine and increases muscle mass as well. Therefore, we thought that it might be of interest to measure BMC in junior competitive weightlifters. On the occasion of a recent Junior World Championship we measured, by single photon absorptiometry, BMC in 59 young competitive male athletes (aged 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
2

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(24 citation statements)
references
References 2 publications
1
20
0
2
Order By: Relevance
“…In this regard, the BMD values presently reported for the lumbar spine and neck of the femur, with respect to age-and race-matched sedentary subjects, are among the highest ever reported. Indeed, similar BMD values have only been previously described in elite male weightlifters [14,19]. The osteogenic potential of physical activities requiring the performance of jumps in unusual directions is supported by other studies also [8,21,22].…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…In this regard, the BMD values presently reported for the lumbar spine and neck of the femur, with respect to age-and race-matched sedentary subjects, are among the highest ever reported. Indeed, similar BMD values have only been previously described in elite male weightlifters [14,19]. The osteogenic potential of physical activities requiring the performance of jumps in unusual directions is supported by other studies also [8,21,22].…”
Section: Discussionsupporting
confidence: 57%
“…High mechanical impact and weight-bearing activities seem more efficient in increasing BMC and BMD than exercise which does not involve impact loading [1][2][3]6,12,14]. Nevertheless, other authors have reported reduced trunk bone mass in professional ballet dancers who generally perform considerable weight-bearing and jumping exercise, although strenuous exercise in girls (particularly if associated with dieting and psychological anxiety) may lead to menstrual disorders and reduced bone mass, thus blunting the beneficial effect of exercise [13].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Virvidakis et al (1990) has provided evidence of increased mineralisation in the non-dominant forearm of competitive weight-lifters aged from 15-20 years.…”
Section: In Crease ¿ a C Tiv Itymentioning
confidence: 99%
“…Research repeatedly shows that ground-based, large muscle group training, such as weightlifting exercises, squatting, and deadlifting, are beneficial in combating bone mineral density concerns [3,4].…”
Section: Introductionmentioning
confidence: 99%